Soil drying and rewatering applied at three grain developmental stages affect differentially growth and grain protein deposition in wheat (Triticum aestivum L.) - Beltrano, José (2006)
Water deficits cause large yield losses in wheat. Although anthesis is generally considered the most vulnerable period, water deficit during grain filling can also cause yield losses. The objective of this study was to investigate the effect of water stress and rewatering, at three different grain developmental stages, on physiological and grain filling parameters and on yield components. Wheat plants were subjected to water deficit and rewatering at the watery ripe, milk and soft dough stages. In the flag leaf, water stress decreased the relative water content, the chlorophyll and protein content and increased the leakage of solutes, at all three studied grain filling stages. Water stress at the watery ripe and milk stages reduced the final grain dry mass by 47 % and 20 %, respectively. This reduction was due to a decrease in the grain filling period and to a significant reduction in the maximum rate of grain-fill. Water stress imposed at the watery ripe stage reduced not only the linear growth phase but also its slope; grain number per spike and the 1000-kernel weight were also significantly reduced. SDS-PAGE patterns of grain proteins at the watery ripe stage did not differ between the controls, stressed or rewatered treatments. Protein patterns at the milk stage changed substantially with water stress, mainly for the high molecular weight glutenin subunits and ω gliadins. Three new bands were observed with apparent molecular weights of 108.5 kDa, 84.8 kDa and 63 kDa. Rewatering reverted water stress effects when it was imposed at the milk stage. Water deficit at the soft dough stage did not have any effect on protein grain patterns.